An In Vivo Study of Low-Dose Intra-Articular Tranexamic Acid Application with Prolonged Clamping Drain Method in Total Knee Replacement: Clinical Efficacy and Safety. (25th October 2015) - Sa-ngasoongsong, Paphon; Chanplakorn, Pongsthorn; Wongsak, Siwadol; Uthadorn, Krisorn; Panpikoon, Tanapong; Jittorntam, Paisan; Aryurachai, Katcharin; Angchaisukisiri, Pantap; Kawinwonggowit, Viroj
Abstract : Background . Recently, combined intra-articular tranexamic acid (IA-TXA) injection with clamping drain method showed efficacy for blood loss and transfusion reduction in total knee replacement (TKR). However, until now, none of previous studies revealed the effect of this technique on pharmacokinetics, coagulation, and fibrinolysis. Materials and Methods . An experimental study was conducted, during 2011-2012, in 30 patients undergoing unilateral TKR. Patients received IA-TXA application and then were allocated into six groups regarding clamping drain duration (2-, 4-, 6-, 8-, 10-, and 12-hours). Blood and drainage fluid were collected to measure tranexamic acid (TXA) level and related coagulation and fibrinolytic markers. Postoperative complication was followed for one year. Results . There was no significant difference of serum TXA level at 2 hour and 24 hour among groups ( p < 0.05 ) . Serum TXA level at time of clamp release was significantly different among groups with the highest level at 2 hour ( p < 0.0001 ) . There was no significant difference of TXA level in drainage fluid, postoperative blood loss, blood transfusion, and postoperative complications ( p < 0.05 ) .   Conclusions . Low-dose IA-TXA application in TKR with prolonged clamping drain method is a safe and effective blood conservative technique with only minimal systemic absorption and without significant increase in systemic absorption over time.